2018
DOI: 10.3390/en11051061
|View full text |Cite
|
Sign up to set email alerts
|

Value-Added Performance and Thermal Decomposition Characteristics of Dumped Food Waste Compost by Pyrolysis

Abstract: Food waste compost has a high Na content, which interferes with plant growth when used as a soil enhancer and therefore makes it difficult to use. And, compared to the amount of compost produced every day, the amount of consumption required in farms is smaller, and the rest is buried underground, which releases greenhouse gases and pollutes underground water. This research compared and analyzed thermal degradation behavior, calorific value, and gas spectrometry during the pyrolysis between food waste compost a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Compost has a lower chlorine content than feedstuff, as the compost is diluted during the washing process (water is added to the food waste to remove salt), and sawdust is added as a moisture-controlling agent. Since the main component of the discharged compost is sawdust [20], it exhibits similar chlorine behavior to other wood-based biomass studies. However, the feedstuff showed a different trend, with chlorine contents closer to the predicted values.…”
Section: Changes In the Structuralized Characteristics According To The Pyrolysis Conditionssupporting
confidence: 67%
See 1 more Smart Citation
“…Compost has a lower chlorine content than feedstuff, as the compost is diluted during the washing process (water is added to the food waste to remove salt), and sawdust is added as a moisture-controlling agent. Since the main component of the discharged compost is sawdust [20], it exhibits similar chlorine behavior to other wood-based biomass studies. However, the feedstuff showed a different trend, with chlorine contents closer to the predicted values.…”
Section: Changes In the Structuralized Characteristics According To The Pyrolysis Conditionssupporting
confidence: 67%
“…There was just a small difference in the carbon contents of the feedstuff and compost, even though carbon is decomposed by microorganisms during composting. This is because the sawdust that was added during composting and microorganisms grown during the decomposition of carbon are included in the compost and collectively released upon pyrolysis [20]. Table 3 shows the primary properties of the food waste compost and feedstuff samples after pyrolysis at different temperatures and retention times.…”
Section: Basic Propertiesmentioning
confidence: 99%
“…For this reason, this study concluded that the pyrolysis of these composts did not seem to be a promising process due to the low values of superior calorific value and biochar. In another study, Lee et al [92] and Giwa et al [93] analyzed the thermal degradation behavior, calorific value and gas spectrometry during pyrolysis among compost from food waste. They concluded that these composts can be used as a promising alternative fuel.…”
Section: Thermogravimetry In Compost Hydrogen Productionmentioning
confidence: 99%
“…Lee et al have studied an alternative for the recovery of food waste compost since the amount generated every day is higher than the amount consumed in farms [3]. Hence, authors have suggested producing biochar from food waste compost using pyrolysis processes.…”
mentioning
confidence: 99%
“…The authors indicate that increased NaCl concentration in the samples inhibited cellulose and lignin decomposition, ultimately increasing the biochar yield by 2.7% for 20%-NaCl concentration. NaCl added in solution state exhibited templating effects, with maximum increase in the Brunauer-Emmett-Teller (BET) surface area and pore volume of 1.23 to 3.50 m 2 •g −1 and 0.002 to 0.007 cm 3 •g −1 , respectively, after washing. Adding a high concentration (20%) of NaCl reduced the BET surface area.…”
mentioning
confidence: 99%